2003
DOI: 10.1074/jbc.m208868200
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-mediated Ca2+ Influx Regulates Growth Plate Chondrocyte Maturation and Apoptosis

Abstract: Maturation of epiphyseal growth plate chondrocytes plays an important role in endochondral bone formation. Previously, we demonstrated that retinoic acid (RA) treatment stimulated annexin-mediated Ca 2؉ influx into growth plate chondrocytes leading to a significant increase in cytosolic Ca 2؉ , whereas K-201, a specific annexin Ca 2؉ channel blocker, inhibited this increase markedly. The present study addressed the hypothesis that annexin-mediated Ca 2؉ influx into growth plate chondrocytes is a major regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
89
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 52 publications
5
89
0
1
Order By: Relevance
“…24,26,27 Activation of apoptotic endonucleases 28 eliciting DNA cleavage and chromatin condensation has been well documented. 29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth. In fact, apoptosis can be induced by Ca 2 þ mobilization from intracellular pools, 23,24,27 chelation of intracellular Ca 2 þ with 1,2-bis-(2-aminophenoxy)ethane-N,N,N 1 ,N 1 -tetra-acetic acid tetra-acetoxymethyl ester (BAPTA-AM) 28,29 or removal of extracellular Ca 2 þ .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…24,26,27 Activation of apoptotic endonucleases 28 eliciting DNA cleavage and chromatin condensation has been well documented. 29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth. In fact, apoptosis can be induced by Ca 2 þ mobilization from intracellular pools, 23,24,27 chelation of intracellular Ca 2 þ with 1,2-bis-(2-aminophenoxy)ethane-N,N,N 1 ,N 1 -tetra-acetic acid tetra-acetoxymethyl ester (BAPTA-AM) 28,29 or removal of extracellular Ca 2 þ .…”
mentioning
confidence: 99%
“…29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth. In fact, apoptosis can be induced by Ca 2 þ mobilization from intracellular pools, 23,24,27 chelation of intracellular Ca 2 þ with 1,2-bis-(2-aminophenoxy)ethane-N,N,N 1 ,N 1 -tetra-acetic acid tetra-acetoxymethyl ester (BAPTA-AM) 28,29 or removal of extracellular Ca 2 þ . 32 Intracellular Ca 2 þ deficiency regulates gene expression 22,26 and induces apoptosis through caspases activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the higher extracellular Ca 2+ , the annexins bind phosphatidylserine in a calcium-dependent manner and act as Ca 2+ channels, allowing an influx of Ca 2+ into the matrix vesicle. Interactions with Type II and Type X collagen stimulate the activity of annexin V by 2-3-fold (Kirsch et al, 2000;Wang et al, 2003), allowing close regulation of the site of nucleation in the extracellular matrix (Fig. 2D).…”
Section: Model Of Extracellular Mineralization In Bone Suggests Mechamentioning
confidence: 99%
“…The activity of annexin family members are crucial for initiating increases in intravesicular Ca 2+ within the matrix vesicles of developing bone only when the vesicle is in contact with the correct extracellular matrix (collagens II and X) (Anderson, 2003;Kirsch et al, 2000;Wang et al, 2003). Studies of annexin homologues in the zebrafish have not identified expression of these proteins in the inner ear-despite whole-mount in situ hybridization at the appropriate time points (Farber et al, 2003).…”
Section: Model Of Extracellular Mineralization In Bone Suggests Mechamentioning
confidence: 99%